2018
DOI: 10.1186/s12906-018-2086-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activities of Guang-Pheretima extract in lipopolysaccharide-stimulated RAW 264.7 murine macrophages

Abstract: BackgroundGuang-Pheretima, which is originated from Pheretima aspergillum, has been documented in academic Chinese herbal studies for nearly 2000 years for its prominent treating effects of various inflammatory diseases such as asthma, cough and fever. However, the anti-inflammatory activity and mechanism of Guang-Pheretima has been rarely reported. Hence, we investigated the inhibitory effect and the underlying mechanism of Guang-Pheretima aqueous extracts on inflammatory response in RAW 264.7 cells.MethodRAW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…The murine macrophage RAW264.7 cells were obtained from the American Type Culture Collection (ATCC), and cultured at 37 °C in the DMEM medium supplemented with the 10% FBS and 1% penicillin-streptomycin in a humidified incubator containing 5% CO 2 . The nitrite production was measured according to the Griess reagent protocol [33]. Briefly, the cells were transferred into the 96-well plate (4–6 × 10 4 cells in each well) and incubated for 24 h. Then, those cells were cultured with serial dilution (11.11, 33.33, 100 μg/mL) of leaves and seeds extracts of M. oleifera for 2 h. Next, those cells were added with the 10 ng/mL of LPS for another 24 h. Then, 100 μL of the culture medium were mixed with the equal volume of the Griess reagent, and after 15 min of reaction, the mixture absorbance was read at 540 nm with a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…The murine macrophage RAW264.7 cells were obtained from the American Type Culture Collection (ATCC), and cultured at 37 °C in the DMEM medium supplemented with the 10% FBS and 1% penicillin-streptomycin in a humidified incubator containing 5% CO 2 . The nitrite production was measured according to the Griess reagent protocol [33]. Briefly, the cells were transferred into the 96-well plate (4–6 × 10 4 cells in each well) and incubated for 24 h. Then, those cells were cultured with serial dilution (11.11, 33.33, 100 μg/mL) of leaves and seeds extracts of M. oleifera for 2 h. Next, those cells were added with the 10 ng/mL of LPS for another 24 h. Then, 100 μL of the culture medium were mixed with the equal volume of the Griess reagent, and after 15 min of reaction, the mixture absorbance was read at 540 nm with a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were maintained at 37 °C in DMEM medium supplemented with the 10% FBS, 1% penicillin–streptomycin with 5% CO 2 in a humidified incubator. The nitrite concentration, an indicator of the NO synthesis, was measured based on the previously described Griess reaction method [ 42 ]. Briefly, RAW 264.7 cells were transferred into the 96-well plate with a density of 5 × 10 4 cells/well and kept for 24 h. These cells were incubated with various concentrations of the SPRE solution for 2 h and then followed by the incubation with 10 ng/mL of LPS for another 24 h. Meanwhile, 10.0 μg/mL of aspirin was used as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…49,50 Previous reports have shown that Pheretima could exert anti-inflammatory effects by reducing the production of inflammatory mediators such as NO, PGE2, TNF-α and various inflammatory cytokines. 51 There is a research revealed that Pheretima may have anti-coagulant and anti-thrombotic functions through regulating DPf3, which is a group of antithrombotic functional proteins purified from Pheretima. 52 Moreover, Bombyx Batryticatus has been reported to exhibit pharmacological activity on the nervous system, such as anticonvulsant and antiepileptic effects, hypnotic effects, and neurotrophic effects and so on.…”
Section: Discussionmentioning
confidence: 99%